2017
DOI: 10.1289/ehp425
|View full text |Cite
|
Sign up to set email alerts
|

Passive Sampling for Indoor and Outdoor Exposures to Chlorpyrifos, Azinphos-Methyl, and Oxygen Analogs in a Rural Agricultural Community

Abstract: Background: Recent studies have highlighted the increased potency of oxygen analogs of organophosphorus pesticides. These pesticides and oxygen analogs have previously been identified in the atmosphere following spray applications in the states of California and Washington. Objectives: We used two passive sampling methods to measure levels of the ollowing organophosphorus pesticides: chlorpyrifos, azinphos-methyl, and their oxygen analogs at 14 farmworker and 9 non-farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
1
22
2
Order By: Relevance
“…2005 , 2009 ). In addition, recent studies report that outdoor air samples from homes located more than from fruit orchards had significantly lower concentrations of two OP pesticides than did samples from homes within of orchards ( Gibbs et al. 2017 ) and average pesticide concentrations in house dust were 64% lower in homes located compared to from treated fields ( Deziel et al.…”
Section: Discussionmentioning
confidence: 99%
“…2005 , 2009 ). In addition, recent studies report that outdoor air samples from homes located more than from fruit orchards had significantly lower concentrations of two OP pesticides than did samples from homes within of orchards ( Gibbs et al. 2017 ) and average pesticide concentrations in house dust were 64% lower in homes located compared to from treated fields ( Deziel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, these chemicals have been found in different matrices, including dietary products, water, outdoor and indoor air and house dust (Banerjee et al, 2012;Sousa et al, 2018;Coscollà et al, 2017;Gibbs et al, 2017;Mercier et al, 2011;Tang et al, 2018). In addition, recent studies have found them even in freshwater and edible fish (Arisekar et al, 2019;Barbieri et al, 2019;Pico et al, 2019), being in some cases related with pollution accidents, like the death fish episode by pyrethroid exposure in Northern Italy (Bille et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We also collected and adjusted for multiple potential confounding factors, including acculturation and socioeconomic factors that have been previously shown to correlate with pesticide levels in house dust 19 , and may also affect where one chooses to live 47 49 . To our knowledge, only one recent study of pesticide drift has used the CropScape data 50 . This recent study, however, investigated the association between distance to orchard and OP concentrations within indoor air and was not large enough to estimate the association independent of number of farmworkers within the household 50 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one recent study of pesticide drift has used the CropScape data 50 . This recent study, however, investigated the association between distance to orchard and OP concentrations within indoor air and was not large enough to estimate the association independent of number of farmworkers within the household 50 .…”
Section: Discussionmentioning
confidence: 99%